Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Cooperative Learning Tipe Talking Stick di Sekolah Dasar - Nindya Mai Syafitri; Zainal Abidin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
This research is motivated by integrated thematic learning that has not been implemented properly in school and still has to be developed as well as possible, this has an impact on the process and learning outcomes of integrated thematic learning which are still not optimal. This study aims to improve student learning outcomes in integrated thematic learning with the Talking Stick Cooperative Learning model in class V SDN 06 Padang Besi. This research is a classroom action research by combining qualitative and quantitative approaches. The data from this study were obtained from lesson plans, observation of student aspects of teacher aspects, action and test results, the data sources in this study were lesson plans and the implementation of learning and the results of integrated thematic learning using the learning model. The research procedure consisted of planning, implementing, observing, and The subjects in this study were teachers and fifth grade students of SDN 06 Padang Besi where the number of male students was 27 and 7 female students. The results showed that in a) Planning in cycle I an average value of 76.79% with qualification (B), increased in cycle II, namely obtaining an average of 92.85% with qualification (A), b) Implementation of cycle I in teacher activity averaged 80.35% with qualifications (B), increased in cycle II to 96.42% with qualifications (A). The implementation of the first cycle in student activities on average 76.79% with qualifications (B), increased in the second cycle to 96.42% with qualifications (A). c) The results in the first cycle the average value of knowledge and skills was 71.9 with qualifications (C), increased in the second cycle, namely obtaining an average value of knowledge and skills was 90.3 with good qualifications (B). This study shows that the Talking Stick Cooperative Learning model can improve learning outcomes in integrated thematic learning.